Linear Vitamin A Requirements for Maternal Health and Reproduc-tive Performance in African Catfish (Clarias gariepinus) - Okure, Godswill; Udo, Imefon; Afia, Ofonime (Journal of Aquaculture and Fish Health, 2025)
A 180-day feeding experiment was conducted in three phases of sixty (60 days each, designated as F0, F1, and F2. The preliminary phase was conducted to detoxify the brood fish of cellular VA. The second and third phases were conducted to assess the first and second spawning seasons. During the preliminary phase, experimental fish were fed with the basal diet thrice a day with three percent fresh body weight to detoxify the fish of residual Vitamin A. A two-generation (F1 and F2) feeding trial evaluated the impact of graded vitamin A supplementation levels on broodstock performance. Three replicate groups of 20 fish (initial weight: 1.60 ± 0.38 kg) were fed one of five isocaloric and isonitrogenous diets, containing 0, 1666, 3332, 6664, or 13,328 IU/kg of vitamin A, at three meals per day. Growth performance, feed utilization, and Survival rate all improved with increased levels of VA and were significantly better (P< 0.05) in F2. Mean GSI, HSI, total fecundity, and relative fecundity. Signs of vitamin A deficiency, including growth retardation and suboptimal feed conversion, were evident in fish receiving the unsupplemented diet (0 IU kg-1). Fortification of the brood stock fish diet of C. Gariepinus and maternal age resulted in improved reproductive performance. The aquaculture industry should formulate broodstock rations with 13,328 IU kg-1 diet of VA inclusion and select mature female broodstock for artificial breeding.